PENGARUH PELATIHAN-PENGEMBANGAN DAN MOTIVASI TERHADAP PENINGKATAN KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASI - Yan Kurnia Hendrawan; Salamah Wahyuni (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
The purpose of this researces was to examine the effect of training and development, motivation, and organizational commitment on employee performance, to examine the effect of training-development and motivation on employee performance mediated by organizational commitment. The Study sample are 75 employee of PT. PLN (Persero) P3BJB APP Madiun consist of 50 employee of APP Madiun and 25 employee of Substation of APP Madiun. Sampling Technique is a purposive sampling dan data collection technique is convenience sampling.The Research shows that training and development has little influence on employee performance directly while indirectly are significant. Motivation and Organizational Commitment shows that has a significant influence on employee performance either directly or indirectly. And also organizational commitment mediates the effect of training-development and motivation on employee performance in PT. PLN (Persero) P3BJB APP Madiun.